2012
DOI: 10.1182/blood-2012-02-409995
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of highly restricted regions in the β-propeller domain of αIIb by platelet-associated anti-αIIbβ3 autoantibodies in primary immune thrombocytopenia

Abstract: AbstractPlatelet-associated (PA) IgG autoantibodies play an essential role in primary immune thrombocytopenia (ITP). However, little is known about the epitopes of these Abs. This study aimed to identify critical binding regions for PA anti-αIIbβ3 Abs. Because PA anti-αIIbβ3 Abs bound poorly to mouse αIIbβ3, we created human-mouse chimera constructs. We first examined 76 platelet eluates obtained from patients with primary ITP. Of these, 26 harbored PA anti-αIIbβ3 Abs (34%). Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…However, in this and other studies a direct correlation between the platelet count and severity of bleeding was not uniformly demonstrated, reflecting the observation that occasional individuals with very low platelet counts exhibit little bleeding, while others with platelet counts > 30 × 10 9 /L bleed frequently. This conundrum might be explained by binding of some antiplatelet antibodies to highly restricted regions in GP IIb β-propeller domain 66 near the ligand (fibrinogen) binding site, potentially interfering with platelet aggregation.…”
Section: Clinical Features Of Itpmentioning
confidence: 99%
“…However, in this and other studies a direct correlation between the platelet count and severity of bleeding was not uniformly demonstrated, reflecting the observation that occasional individuals with very low platelet counts exhibit little bleeding, while others with platelet counts > 30 × 10 9 /L bleed frequently. This conundrum might be explained by binding of some antiplatelet antibodies to highly restricted regions in GP IIb β-propeller domain 66 near the ligand (fibrinogen) binding site, potentially interfering with platelet aggregation.…”
Section: Clinical Features Of Itpmentioning
confidence: 99%
“…More detailed epitope mapping using serial human/mouse chimera αIIb showed that the Abs mainly recognized the W3:4‐1 loop in the β‐propeller domain of αIIb. Thus, the epitopes of the Abs in this patient were not so unique but were located on one of the major recognition sites of anti‐αIIbβ3 Abs detected in chronic ITP (Figure S6) .…”
Section: Resultsmentioning
confidence: 86%
“…However, we detected neither inhibition nor activation of αIIbβ3 by anti‐αIIbβ3 autoAbs of the patient. We hypothesized that the patient's Abs recognize a unique epitope of αIIbβ3 and performed epitope mapping as previously described . However, the patient's Abs recognized common recognition sites of PA anti‐αIIbβ3 autoAbs detected in chronic ITP patients, suggesting that the difference in epitope does not account for the unique phenotype of the patient's platelets.…”
Section: Discussionmentioning
confidence: 98%
“…Primary ITP is an autoimmune disorder characterized by isolated thrombocytopenia due to accelerated PLT destruction and impaired PLT production . Thrombocytopenia is frequently encountered in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Primary ITP is an autoimmune disorder characterized by isolated thrombocytopenia due to accelerated PLT destruction and impaired PLT production. 1,2 Thrombocytopenia is frequently encountered in patients with cancer. This is commonly caused by bone marrow infiltration of malignant cells, cancerinduced disseminated intravascular coagulation, thrombotic thrombocytopenic purpura, and intratumor hemorrhage.…”
Section: Discussionmentioning
confidence: 99%